To convert an intercept form of a quadratic equation to standard form, you start with the intercept form, which is given by:
y = a(x – p)(x – q)
Here, p and q are the x-intercepts of the quadratic, and a is a coefficient that affects the width and direction of the parabola.
Follow these steps to convert it:
- Expand the factors: Distribute the expression:
- Start by multiplying the two binomials:
- Multiply by ‘a’: Now, multiply the entire expression by ‘a’:
- Reorganize into standard form: The standard form of a quadratic is:
(x – p)(x – q) = x² – (p + q)x + pq
y = a(x² – (p + q)x + pq) = ax² – a(p + q)x + apq
y = Ax² + Bx + C
Therefore, you can now see your equation is:
y = ax² + (-a(p + q))x + apq
In this form, A = a, B = -a(p + q), and C = apq. That’s how you successfully convert the intercept form of a quadratic equation to its standard form!